Pathology of the Heart in the Qur’ān: A Metaphysico-psychological Explanation - Ahmad, Absar (Intellectual Discourse, 1999)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> According to the Qur’ān, heart is the faculty by means of which an individual grasps the truth of ultimate moral and metaphysical verities. These functions can be disturbed-a condition which the Qur’ān refers to as diseases of the heart-due to a number of reasons. This article examines the nature and aetiology of the "diseases of heart" in the light of the Qur’ān. Human tendencies towards placidity, complacency and self-satisfaction, and the more dangerous capacity of self-deceptions, lead to the destruction of the inner vision and spiritual vigour, and to a "diseased" heart.